2018
DOI: 10.1038/s41598-018-32328-y
|View full text |Cite
|
Sign up to set email alerts
|

Balance design for robust foliar nutrient diagnosis of “Prata” banana (Musa spp.)

Abstract: The “Cavendish” and “Prata” subgroups represent respectively 47% and 24% of the world banana production. Compared to world average progressing from 10.6 to 20.6 t ha−1 between 1961 and 2016, and despite sustained domestic demand and the introduction of new cultivars, banana yield in Brazil has stagnated around 14.5 t ha−1 mainly due to nutrient and water mismanagement. “Prata” is now the dominant subgroup in N-E Brazil and is fertigated at high costs. Nutrient balances computed as isometric log-ratios (ilr) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…Table 4 presents the results regarding taste sensory analysis. It is observed that the fruits treated with biofilm and evaluated at 7 days were considered the best, obtaining the highest score (5) and differing from all treatments and evaluation periods, indicating that biofilm at 7 days of storage at room temperature, in addition to replacing refrigeration in the mass preservation, also presented the best flavor, mainly due to the higher °Brix observed (Table 1), enabling the physiological changes caused by ethylene, without fruit degradation. Thus, it could be concluded that the low temperature provided by refrigeration is able to delay the ripening process of 'Prata' banana, preserving its measurable characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 presents the results regarding taste sensory analysis. It is observed that the fruits treated with biofilm and evaluated at 7 days were considered the best, obtaining the highest score (5) and differing from all treatments and evaluation periods, indicating that biofilm at 7 days of storage at room temperature, in addition to replacing refrigeration in the mass preservation, also presented the best flavor, mainly due to the higher °Brix observed (Table 1), enabling the physiological changes caused by ethylene, without fruit degradation. Thus, it could be concluded that the low temperature provided by refrigeration is able to delay the ripening process of 'Prata' banana, preserving its measurable characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…From these varieties, new varieties originated by natural mutation. 'Branca' variety originated all varieties of the 'Prata' subgroup, directly, as in the case of 'Prata', 'Prata-Anã' and 'SCS451 Catarina', or indirectly, as in the case of 'Pacovan' and 'Prata-Gorutuba' [4], with 'Prata' subgroup representing 24% of world banana production [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have verified that SVM performs better than Naïve Bayes dealing with unbalanced classes [52][53][54]. Moreover, the feature vector transformation using ILR alleviates the unbalanced problem as it is suggested in [55].…”
Section: Discussionmentioning
confidence: 99%
“…The CND based on clr aimed initially to replace DRIS for regional diagnosis [16,42,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Thereafter, a website service was made available to Brazilian growers (https://www.registro.unesp.br/#!/sites/cnd/).…”
Section: Tissue Nutrient Diagnosismentioning
confidence: 99%